Molecular and neurological features of MELAS syndrome in paediatric patients: A case series and review of the literature. Issue 7 (26th April 2022) - Seed, Lydia M.; Dean, Andrew; Krishnakumar, Deepa; Phyu, Poe; Horvath, Rita; Harijan, Pooja Devi
Abstract: Background: Mitochondrial encephalomyopathy, lactic acidosis and stroke‐like episodes (MELAS) syndrome is one of the most well‐known mitochondrial diseases, with most cases attributed to m.3243A>G. MELAS syndrome patients typically present in the first two decades of life with a broad, multi‐systemic phenotype that predominantly features neurological manifestations––stroke‐like episodes. However, marked phenotypic variability has been observed among paediatric patients, creating a clinical challenge and delaying diagnoses. Methods: A literature review of paediatric MELAS syndrome patients and a retrospective analysis in a UK tertiary paediatric neurology centre were performed. Results: Three children were included in this case series. All patients presented with seizures and had MRI changes not confined to a single vascular territory. Blood heteroplasmy varied considerably, and one patient required a muscle biopsy. Based on a literature review of 114 patients, the mean age of presentation is 8.1 years and seizures are the most prevalent manifestation of stroke‐like episodes. Heteroplasmy is higher in a tissue other than blood in most cases. Conclusion: The threshold for investigating MELAS syndrome in children with suspicious neurological symptoms should be low. If blood m.3243A>G analysis is negative, yet clinical suspicion remains high, invasive testing or further interrogation of the mitochondrial genome should be considered. Abstract : MELAS syndrome is one of the most well described mitochondrial diseases and typically presents during childhood. Patients display a broad, multi‐systemic phenotype with predominantly neurological manifestations, however, marked phenotypic variability has been observed, which creates a significant clinical challenge. Here we report three new clinical cases of paediatrics patients and a review of 114 paediatric cases in the literature, and discuss the clinical characteristics, histopathological features and molecular causes of MELAS syndrome in children, as well as putative molecular mechanisms of phenotypic variability observed in this mitochondrial disorder.